Female reproductive functions of the neuropeptide PACAP - Koppan, Miklos; Nagy, Zsuzsanna; Bosnyak, Inez; Reglodi, Dora (Frontiers in Endocrinology, 2022)
Pituitary adenylate cyclase activating polypeptide (PACAP) is a neuropeptide originally isolated as a hypothalamic peptide. It has a widespread distribution in the body and has a diverse array of actions. Among others, PACAP has been shown to be involved in reproductive processes. In this review we summarize findings related to the entire spectrum of female reproduction. PACAP is a regulatory factor in gonadal hormone production, influences follicular development and plays a role in fertilization and embryonic/placental development. Furthermore, PACAP is involved in hormonal changes during and after birth and affects maternal behavior. Although most data come from cell cultures and animal experiments, increasing number of evidence suggests that similar effects of PACAP can be found in humans. Among others, PACAP levels in the serum shows changes during pregnancy and during birth. PACAP is present in the human follicular and amniotic fluids and in the milk. Levels of follicular fluid PACAP correlate with the number of retrieved oocytes in hyperstimulated women. Human milk has very high levels of PACAP compared to plasma levels, with colostrum showing the highest levels, but concentrations remain steady thereafter during the first 7 months of lactation. All these data demonstrate that PACAP has important functions in reproduction both under physiological and pathological conditions.